방전 플라즈마 소결법으로 제조된, AlN-MgO 소결체의 미세구조와 열적, 기계적 특성 - 모한첸; Mohan Chen; 정명진; Myungjin Jung; 안정원; Jung-won An; 신승용; Seung Yong Shin; 박윤휘; Yunhwi Park; 김선래; Sunrae Kim; et al. (대한금속·재료학회지, 62(5), 2024)
AlN-MgO composites with different compositions were prepared by spark plasma sintering, and the effects of their composition on their microstructure, thermal properties, and mechanical properties were systemically investigated. MgO compositions in the AlN-MgO composites were controlled from 20 to 80 wt%. The results indicated that a phase transition did not occur during the sintering process, and different solid solutions were formed within the MgO and AlN lattices. The AlN-MgO composites exhibited finer-grain microstructures than those of the sintered pure AlN and MgO samples. Transmission electron microscopy analysis showed that both oxygen-rich, low-density grain boundaries and clean boundaries with spinel phases were present in the composites. The sintered pure AlN sample exhibited the highest thermal conductivity (53.2 W/mK) and lowest coefficient of thermal expansion (4.47 × 10 -6 /K) at 100℃. And, the sintered pure MgO sample exhibited moderate thermal conductivity (39.7 W/mK) and a high coefficient of thermal expansion (13.05 × 10 -6 /K). With increasing MgO contents in the AlN-MgO composites, however, the thermal conductivity of the AlN-MgO composites decreased, from 33.3 to 14.9 W/mK, while their coefficient of thermal expansion generally increased, from 6.49×10 -6 to 10.73×10 -6 /K with increasing MgO content. The composite with an MgO content of 60 wt% exhibited the best mechanical properties overall. Thus, the composition and microstructure of AlN-MgO composites have a determining effect on their thermal and mechanical properties. (Received 19 December, 2023; Accepted 4 January, 2024)